467 Cost Effectiveness of Using a New Autograft Harvesting Technology in Adult Posterior Lumbar Spine Fusion Surgery. (1st April 2022) - Gandhoke, Gurpreet S.; Orsheln, Sarah; Smith, Kenneth
Abstract : INTRODUCTION: Autograft in the form of the patient's own bone dust can be harvested during surgery and used to facilitate fusion, or allograft can be purchased at a cost and used as an alternative. METHODS: We compared allograft use to the upfront investment of a new autograft harvesting technology (Bone Collector), enrolling 107 patients. In 81 patients, Bone Collector was used to collect autologous graft. We compared the allograft requirement and allograft cost to similar variables in a control group of 26 patients where the Collector was not utilized. Quality Adjusted Life Years (QALYs) were calculated as the effectiveness parameter for both groups. EQ-5D scores were used to calculate quality of life utilities pre-operatively and at 3 months, 1 year and 2 years post-operatively. The cost-effectiveness study was performed from a societal perspective with a 2-year horizon for US populations. RESULTS: Of the 81 patients for whom the Bone Collector was used, 58% patients required autograft only. Forty-Two percent required allograft supplementation with the harvested autograft. In the 26 patients where the bone collector was not utilized, 35% required autograft only, while 66% required both autograft and allograft. The mean allograft requirement for the Bone Collector group was 4cc, while that of the group not utilizing the Bone Collector was 7.5cc. The cost of Allograft ranged from 100 to 4000. The cost of the 2 different Bone Collectors that were used in this study ranged from 400 to 1000. Preoperative ODI and EQ-5D scores for the entire cohort improved at 3 months, one year and 2 years postoperatively. Our decision analysis revealed that using the Bone collector was dominant (cost saving and more effective) compared to non-use, saving 326 and gaining 0.04 QALYs. Results were robust in multiple sensitivity analyses, with Bone Collector remaining dominant unless its cost is >2900. CONCLUSION: Our cost-effectiveness analysis revealed that Bone Collector would be cost saving and more effective in most plausible scenarios.